Mixing and matching research and innovation policies in EU countries - Reinhilde Veugelers (Bruegel, 2015)
The European Union has prioritised the pursuit of innovation-based growth and targeting of resources to promote research and development, but performance on innovation remains weak. With the lack of results comes fatigue, waning interest and mounting criticism about policy. Should the EU abandon its ambition to become the most innovative region in the world? We examine EU member state research and innovation policies. We assess whether the deployment of innovation policy instruments in EU countries matches their innovation capacity performance relative to other EU countries. We find a relative homogeneity of policy mixes in EU countries, despite the fairly wide and stable differences in their innovation capacities. Our analysis therefore provides a rationale for a more comprehensive review of innovation policy mixes to assess their adequacy in addressing countryspecific innovation challenges.
Keywords: 330